Improving the Lecturers of Musi Charitas Catholic University Speaking Skills through Oral Presentation - Sheilla Noveta Asmaruddin (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
This research is aimed at investigating whether oral presentation technique was able to be used as a way to develop the lecturers of Musi Charitas Catholic University speaking skills, Palembang. This study is a quasi experimental design, specifically, it is a one group pretest posttest one. There were 22 lecturers taken as samples based on availability. These lecturers were from three faculties - Faculty of Business and Accounting; Faculty of Science and Technology; Faculty of Health Science. Training were administered for five days for each lecturers from different faculties. A speaking rubric was used to evaluate the lecturers' speaking skills development by two experts in TESOL. Paired t-test and multiple regression were used as statistical analysis to find the siginificance and the depth of influence of each category of speaking techniques. Those categories were organisation, content and presentation. The significant finding of the research is that oral presentation technique was able to improve the lecturers' speaking skill in terms of talk of performance.